Pediatric Emergency Medicine Physicians' Perceptions of Colleagues' Clinical Performance Over Career Span. Issue 5 (28th May 2023) - Henretig, Fred M.; Wood, Joanne N.; Shea, Judy A.; Schapira, Marilyn M.; Ruddy, Richard M.
Abstract : Objective: The US physician workforce is aging, prompting concerns regarding clinical performance of senior physicians. Pediatric emergency medicine (PEM) is a high-acuity, multitasking, diagnostically complex and procedurally demanding specialty. Aging's impact on clinical performance in PEM has not been examined. We aimed to assess PEM physician's' perceptions of peers' clinical performance over career span. Methods: We surveyed 478 PEM physician members of the American Academy of Pediatrics' Section on Emergency Medicine survey study list-serve in 2020. The survey was designed by the investigators with iterative input from colleagues. Respondents rated, using a 5-point Likert scale, the average performance of 4 age categories of PEM physicians in 9 clinical competencies. Additional items included concerns about colleague's performance and preferences for age of physician managing a critically ill child family member. Results: We received 232 surveys with responses to core initial items (adjusted response rate, 49%). Most respondents were 36 to 49 (34.9%) or 50 to 64 (47.0%) years old. Fifty-three percent reported ever having concern about a colleague's performance. For critical care–related competencies, fewer respondents rated the ≥65-year age group as very good or excellent compared with midcareer physicians (36–49 or 50–64 years old). The ratings for difficult communications with families were better for those 65 years or older than those 35 years or younger. Among 129 of 224 respondents (58%) indicating a preferred age category for a colleague managing a critically ill child relative, most (69%) preferred a 36 to 49-year-old colleague. Conclusions: Pediatric emergency medicine physicians' perceptions of peers' clinical performance demonstrated differences by peer age group. Physicians 65 years or older were perceived to perform less well than those 36 to 64 years old in procedural and multitasking skills. However, senior physicians were perceived as performing as well if not better than younger peers in communication skills. Further study of age-related PEM clinical performance with objective measures is warranted.